Performance Development of Islamic School's Principals in Republic of India in the light of educational Competencies - Saleem, Badruddin Mohammad; Al-Manea, Abdullah Mohammad (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the degree of Islamic school principals in the Republic of India practice educational competencies, and to identify the difficulties of developing their performance and the requirements for developing it in light of those competencies. The researchers used the descriptive approach, questionnaire and interview as tools for the study. The study sample included (287) teachers of private Islamic schools in the District: Siddharth Nagar, Uttar Pradesh, India. The interview was also conducted with (30) principals of Islamic schools in the Siddharth Nagar District in the Republic of India. The results of the study revealed that the degree of practicing the competencies among Islamic school principals in the Republic of India reached an average of (2.77 out of 4.00) and a (medium) degree, and the difficulties faced by Islamic school principals in the Republic of India in developing their performance reached an average of (3.24 out of 4.00) and a (medium) degree. While the requirements received a (high) degree of importance, and in light of the results of the study, the researchers recommended urging Islamic school principals to pay more attention to competencies, holding courses and training programs in schools to enhance the concept of technical competencies among school principals, and employing modern technologies for administrative work in schools. Islamic studies in the Republic of India and the need to reduce the teaching burden of school principals. The researchers also suggested the necessity of conducting a similar study in other regions of the Republic of India.
Keywords: performance development; school principal; Islamic schools; competencies; Republic of India